Adjustment in the flight phase of 1m springboard forward pike dives - Sayyah, M.; Yeadon, M. R.; Hiley, M. J.; King, M. A. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to investigate the variability in 1m springboard forward pike dives (101B). Variability of body orientation angle at takeoff and water entry together with joint angle time histories of 15 forward pike dives, performed by an international diver, were determined using video analysis. A computer simulation model was used to investigate the effects of initial conditions variability and flight phase configuration variability on outcome (orientation at entry) variability. It was found that the variation in the simulated orientation at entry arising from variability in the initial conditions was greater than the actual variation. This indicates that the diver used feedback correction to make adjustments during flight to reduce the variability of his entry angle.